Ensuring Fairness in Land Acquisition for Public Road Construction: A Case Study of Badung Regency - Dharmawan, I Made Alit Putra; Wesna, Putu Ayu Sriasih; Utama, I Wayan Kartika Jaya (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
Land acquisition problems in public interest development raise various psychosocial problems in the community so psychosocial aspects must be taken into account along with the role of independent assessment experts and procurement management needed so that the community can receive compensation from the release of their land. The purpose of the author's analysis is related to the land implementation acquisition in Badung Regency and how to resolve land acquisition rejection disputes in Badung Regency. The author uses an empirical legal research method that has a function in showing the real law that exists in people's lives. The results of the study are on land acquisition for public interest for road construction in Badung Regency using the Land Acquisition Procedures and Procedures in accordance with Law Number 2 of 2012, where Badung Regency, especially the Public Works and Spatial Planning Agency of Badung Regency, Highways Sector as an Agency that requires land on a Small Scale, submits a Work Plan that is in accordance with the Badung Regency Medium-Term Development Plan and the existence of land acquisition and rejecting the compensation value has the right to reject land acquisition by filing an objection to the legal institution, namely the State Administrative Court and the District Court in the rejection, in resolving the rejection dispute, Badung Regency in resolving the dispute by means of Litigation and Non-Litigation.